South Sudan : 2016 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for South Sudan. (IMF Staff Country Reports; Country Report ;, 2017)
This 2016 Article IV Consultation highlights the rapid deterioration of economic conditions in South Sudan since the beginning of the civil conflict in late 2013. Real GDP growth declined by nearly 20 percent during 2015 and 2016, and annual inflation rose to about 550 percent in September 2016 before declining to 370 percent in January 2017. The medium-term outlook faces challenges and significant downside risks. Without significant progress toward peace and economic stabilization, the economic trajectory for South Sudan is highly unstable, and the country risks spiraling into a trap of deteriorating economic performance and worsening security with continued high humanitarian costs.